Зниження впливу золошлаконакопичувача сумської тец на гідросферу - Пляцук, Леонід Дмитрович; М'якаєва, Ганна Миколаївна; М'якаєв, Олександр Володимирович (НТУ "ХПІ", 2018)
Представлені дослідження впливу золошлаконакопичувача Сумської ТЕЦ на підземні води. За результатами моніторингу встановлено, що в підземних водах першого від поверхні водоносного комплексу спостерігається зміна хімічного складу за рахунок фільтрації вод із золовідвалу. Ознаками цього є підвищений вміст у воді із спостережних свердловин хлоридів, сульфатів, натрію, заліза. Для запобігання забрудненню підземних і поверхневих вод запропоновано створення техногенного геохімічного бар'єру. З метою вибору матеріалу для екрану досліджувались природні глини Сумської області. Встановлена присутність в глинистих матеріалах Сумського району смектитових мінералів, які забезпечують високу сорбційну здатність до іонів важких металів. Проведені дослідження показали, що іони важких металів входять структуру глин та не вимиваються з них опадами, що дозволяє рекомендувати глини Сумського району для створення протифільтраційного екрану золошлаконакопичувача Сумської ТЕЦ.

The aim of the work is to develop measures of reducing the impact of the ash and slug dump of the Sumy Thermal Power Plant on the environment. Investigation of the factors of impact of the ash and slug dump of the Sumy Thermal Power Plant on groundwater showed that there is a significant amount of heavy metals in the ash and slags of Sumy TPP. As a result of the contact of a slag mixture with atmospheric precipitation they can leak out, move into soluble forms and pollute soils and groundwater. The radioactivity of a mixture of ash slag is 18 mR / h. Ash and slag have the following physical and mechanical characteristics: the bulk density is 1350 kg/m3, the filtration coefficient is 3.5 m/day. The location of ash and slug dump of the Sumy Thermal Power Plant close to the Psel river and the insufficient protection of the groundwater leads to the migration of pollutants. Signs of this are the high content in the water from the observation wells of chlorides, sulfates, sodium and iron. The results of researches of groundwater of the first from the surface aquifer at the site of the ash and slug dump indicate the changes in its chemical composition by water filtration from the ash and slug dump.
Reduction of the influence of ash and slug dump of sumy TPP on the hydrosphere
Keywords: теплова електростанція; золовідвал; важкі метали; міграція; екран; глина; thermal power plant; heavy metals; migration